Model Integrasi Lingkungan Bisnis – Strategi Operasi – Kinerja Perusahaan, Studi Empiris pada Perusahaan Manufaktur Menengah Besar di Tasikmalaya - Edy Suroso (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
This research is to develop a theoretical model about performance and to test the influence of business environment in determining operations strategy and to improve company performance by empirical test in high medium manufacturing company in Tasikmalaya.This is explanatory research. The method of the research is survey. The object of the research consists of business environment, operations strategy and performance. The research location is in Tasikmalaya City and Regency involving the high medium manufacturing companies. The research subject is CEO. The research population is 192 high medium manufacturing companies in Tasikmalaya. The research sample is 110 companies determined by Structural Equation Model, as the method of analysing data, which is operated by AMOS. The conclusions of the research are: (1) Business environment sets a significant role in determining operations strategy choice, so to decide the competitive company priority needs the right identified scanning environment. (2) The success of the company in uncertainty business condition will be reached if the company is able to focus itself in cost strategy, quality strategy and delivery strategy.Keywords: business environment, operations strategy, performance and balance score card